Utilization of Osseous Landmarks for Anatomic Anterior Cruciate Ligament Femoral Tunnel Placement - Rowan, Flynn Andrew; Marshall, Tyler; Gombosh, Michael R.; Farrow, Lutul Dashaun (The Journal of Knee Surgery, 2017)
Accurate placement of the femoral tunnel is critical for long-term clinical success following anterior cruciate ligament (ACL) reconstruction. The purpose of the present study is to evaluate the accuracy of femoral tunnel placement when referencing osseous landmarks during ACL reconstruction. We hypothesize that referencing osseous landmarks during ACL reconstruction consistently results in anatomic placement of the ACL femoral tunnel. This study was a retrospective case series. We reviewed 83 consecutive ACL reconstructions performed by a single surgeon. The lateral intercondylar ridge and lateral bifurcate ridge were referenced intraoperatively for anatomic placement of the ACL femoral tunnel during single-bundle reconstruction. Using these landmarks, the femoral tunnel was placed in the center of the anteromedial bundle footprint on the lateral wall of the intercondylar notch. We reviewed all operative notes and intraoperative arthroscopic images to assess tunnel placement. Postoperative anteroposterior and lateral radiographs were obtained in all patients. Anatomic placement was confirmed by review of lateral radiographs utilizing both the quadrant method (QM) and Blumensaat-ridge ratio (BRR). We used a total of 80 patients for our study. Review of arthroscopic images confirmed anatomic placement of the ACL femoral tunnel in all patients. All patients demonstrated that the femoral tunnel was placed anatomically according to the BRR method. Using the QM, all femoral tunnels were placed anatomically except for one tunnel that was placed slightly anteriorly. There was excellent agreement between the two radiographic measurement techniques. The principal finding of this study indicates that the lateral intercondylar ridge and the lateral bifurcate ridge are reliable landmarks for anatomic placement of the ACL femoral tunnel. Referencing osseous landmarks during surgery can help surgeons avoid nonanatomic placement of the ACL femoral tunnel, especially in cases where the soft-tissue footprint is no longer present. Furthermore, both the radiographic QM and the BRR are valid techniques to assess for anatomic ACL femoral tunnel placement both intraoperatively and postoperatively.
Keywords: anterior cruciate ligament; lateral intercondylar ridge; quadrant method; Blumensaat-ridge ratio; femoral tunnel